Barriers of breast self-examination among Omani women - Zalikha Al-Marzouqi; Noora S Al-Jabri; Aida Al-Dhoani; Iman Al-Risi (Advances in Biomedical and Health Sciences)
Background: Breast cancer is one of the most life-threatening health issues in women and an exceptionally fatal disorder. Breast cancer can be addressed through health education and proper screening such as breast self-examination (BSE). Therefore, we aimed to investigate the knowledge, practices, and barriers to BSE among women in Oman. Methods: We used a nonexperimental, quantitative, cross-sectional design, with data collected at a single point. This study was conducted in the North Batinah Governorate in Oman with 533 women from various primary healthcare institutions. Results: The study revealed that over 80% of the women surveyed were aware of breast cancer, and 70% had a good understanding of BSE. However, practicing BSE was challenging. Only a small percentage of women (10.1%, n = 54) regularly performed BSE every month, and a minority (25.9%, n = 138) started performing BSE at the age of 20 years. Approximately, over half of the women (n = 269) occasionally practiced BSE, while 54% (n = 288) started practicing BSE at the age of 40 years. Conclusion: This study revealed several barriers to BSE. These barriers include the practical aspects of BSE, fear of a potential breast cancer diagnosis, and embarrassment associated with BSE. This study is necessary and crucial for mothers, healthcare professionals, and policymakers, as it furthers the knowledge of BSE within the Omani context. The significance of this study cannot be magnified, as it directly affects the health and well-being of Omani women, emphasizing the urgent demand for action.